Scanning Environmental at Private High School Cilegon City, Banten Province - Djabidi, Faizal; Wasliman, Iim; Juhji, Juhji (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2021)
This study describes and analyses environmental scanning at private high schools in Cilegon City, Banten Province. This research was conducted at three private high schools in Cilegon City, namely Rauhatul Jannah Islamic Integrated High School, Al-Khairiyah 4 High School and Muhammadiyah High School, using qualitative research methods with a case study approach. Principals, vice principals, and teachers from the three schools became research sources. The results of the study found that school strengths are student achievement in academic and non-academic fields, extracurricular activities, qualified and competent educators, collaboration with stakeholders, vision and mission as well as organizational programs, effective school planning, having guidelines, infrastructure, curriculum, school culture, deliberation and effective communication with the internal and external environment. The school's weaknesses have not yet maximized realizing the vision, mission and learning process, enforcement of school rules, lack of management and supervision, lack of school financial funding. School opportunities: academic and non-academic achievements, being the choice of students and parents, increasing new student registrants exceeding the quota, becoming a reference for comparative studies, entrepreneurial and entrepreneurial programs, becoming a model school model, good supervisory communication with relevant agencies and school committees. Threats to schools are limited and lack of financial resources, locations close to state schools, equivalent schools, new competitors who have the same platform, hostile behaviour and activities of students, less conducive school environment. Given the importance of scanning the school environment as one of a series of strategic plans, it is proper that the scanning of the school environment should be carried out carefully, thoughtfully and using the scientific method.